Coastal Damage Management Model Based on Coastal Community in Buleleng Regency - Wesnawa, I Gede Astra (International Research Journal of Management, IT & Social Sciences, 2017)
This research was conducted in North Coastal of Buleleng Regency Bali Province, for two years. The second year aims to assess: (1) how the refinement of the conceptual model of community-based management of coastal damage, and (2) evaluation of the conceptual model of community-based management of coastal damage. Based on population distribution in a district that has a beach, then selected three representative Buleleng Regency, there is in West Buleleng is taken samples in Seririt District, in Central Buleleng represented by Buleleng District and in Eastern Buleleng is Kubutambahan District. Three areas were selected purposively with the consideration that the beaches in the area most damaged either due by coastal erosion and human intervention in the utilization of resources in the northern coastal areas of Bali. The data collected in this study included primary data and secondary data, collected using a data collection instrument. Data analysis was conducted using qualitative descriptive analysis.Â